Initial Colonization, Nutrient Supply, and Fungal Activity on Leaves Decaying in Streams - Sridhar, K. R. (American Society for Microbiology, 2000)
Aquatic hyphomycetes dominate leaf decomposition in streams, and their biomass is an important component in the diet of leaf-eating invertebrates. After 2 weeks of exposure in a first-order stream, maple leaf disks had low levels of fungal biomass and species diversity. Spore production by aquatic hyphomycetes also was low. Subsets of these disks were left in the stream for another 3 weeks or incubated in defined mineral solutions with one of three levels of nitrate and phosphate. Stream disks lost mass, increased ergosterol levels and spore production, and were colonized by additional fungal species. External N and P significantly stimulated mass loss, ergosterol accumulation, and spore production of laboratory disks. On disks incubated without added N and P, ergosterol levels declined while conidium production continued, suggesting conversion of existing hyphal biomass to propagules. In all other treatments, approximately equal amounts of newly synthesized biomass were invested in hyphae and conidia. Net yield (fungal biomass per leaf mass lost) varied between 1% (in the laboratory, without added N or P) and 31% (decay in stream). In most treatments, the three aquatic hyphomycete species that dominated spore production during the first 2 weeks in the stream also produced the largest numbers of conidia in the following 3 weeks. Principal-component analysis suggested two divergent trends from the initial fungal community established after 2 weeks in the stream. One culminated in the community of the second phase of stream exposure, and the other culminated in the laboratory treatment with the highest levels of N and P. The results suggest that fungal production in streams, and, by extension, production of invertebrates and higher tropic levels, is stimulated by inorganic N and P.